CERAMAH (CEK TEKANAN DARAH DIRUMAH) - Vivin Wiji Astutik; Alvin Abdillah; Selvia Nurul Qomari (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
Ceramah is a community empowerment and education program for the community that is oriented towards improving the quality of human resources for hypertension, especially for pregnant women. The prevalence of hypertension based on the diagnosis of health professionals and measurement results seems to increase with increasing age, number of children and pregnancy interval. The existence of this program brings benefits, the community, especially pregnant women or women who plan pregnancy more regularly, to check blood pressure, the community is closer to health services, their health is more controlled, and the community can be involved in improving life with Puskesmas Arosbaya partners. The problems experienced by partners, the role of health cadres are not effective and optimal, and access to health services is far away. But even though they are far from health services, they are very enthusiastic about finding out and participating in health activities. The strategies are routine blood pressure checks, counseling on hypertension in pregnancy, training in blood pressure checks for active cadres and communities, and continuing to provide secondary prevention with health education via short messages using cellphones and free consultation by village midwives. The methods used are mini-workshop, lecture, and cadre training. The output target is to optimize the prevention of hypertension in pregnant women, closer to health service facilities and increase public understanding of hypertension in pregnant women in Dusun Krojeh, Desa Glagah, Kecamatan Arosbaya.